2015
DOI: 10.5301/ejo.5000661
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Reticular Pseudodrusen in Eyes with Newly Presenting Neovascular Age-Related Macular Degeneration

Abstract: Reticular pseudodrusen have a high prevalence in eyes presenting with nAMD (22.1%), although at rates much lower than that of conventional drusen. They are largely a bilateral finding, occurring more frequently in women. Unlike other previous reports, we found no difference in their occurrence between the different subtypes of CNV including RAPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Overall, use of at least two modalities may be recommended to detect and confirm the diagnosis of reticular lesions. 5,[9][10][11]13,[15][16][17]29,30 In the Beaver Dam Study, drusen type was related to the 15-year incidence of RPD (OR per more severe drusen type [hard distinct < soft distinct < soft indistinct]: 1.37) but not to drusen location or area. In the Blue Mountains Eye Study, 10 the location of any soft drusen at close proximity to the fovea (OR: 2.2) and an area of soft drusen between 375 lm and 0.5 disc area in diameter (OR: 3.2) were significantly associated with a greater risk of reticular drusen.…”
Section: Discussion Prevalencementioning
confidence: 99%
“…Overall, use of at least two modalities may be recommended to detect and confirm the diagnosis of reticular lesions. 5,[9][10][11]13,[15][16][17]29,30 In the Beaver Dam Study, drusen type was related to the 15-year incidence of RPD (OR per more severe drusen type [hard distinct < soft distinct < soft indistinct]: 1.37) but not to drusen location or area. In the Blue Mountains Eye Study, 10 the location of any soft drusen at close proximity to the fovea (OR: 2.2) and an area of soft drusen between 375 lm and 0.5 disc area in diameter (OR: 3.2) were significantly associated with a greater risk of reticular drusen.…”
Section: Discussion Prevalencementioning
confidence: 99%
“…In individuals with newly diagnosed choroidal neovascularisation 17–58 per cent have been found to have RPD . Care needs to be taken when considering RPD presence in the context of choroidal neovascularisation as development of choroidal neovascularisation has been observed to result in RPD fading …”
Section: Clinical Implications and Relationship With Amdmentioning
confidence: 99%
“…Multiple‐subtypes of choroidal neovascularisation have been described in association with RPD including types 1, 2 and 3 choroidal neovascularisation, vascularised pigment epithelial detachment, and haemorrhagic and fibrotic scarring . Type 3 choroidal neovascular membranes, also referred to as retinal angiomatous proliferation and retinal choroidal anastomosis, have been shown to have particular association with RPD, occurring more frequently with RPD than without …”
Section: Clinical Implications and Relationship With Amdmentioning
confidence: 99%
“…When adjusted for age, their 15-year cumulative incidence has been shown within the BMES to be twice more likely in females compared to males (5.6 vs 2.2%). 2,3,7,8,33 Arnold et al 2 reported 87% of patients with RPD were female, and Klein et al 9 demonstrated that the prevalence of RPD to be 2.5 times higher in woman within normal subjects. Similarly, in the BMES, after adjusting for age, Joachim et al 8 demonstrated the 15-year cumulative incidence of RPD was twice as likely in females.…”
Section: Discussionmentioning
confidence: 99%
“…Since then several groups have reported a high prevalence of RPD in eyes with both geographic atrophy (GA) and nAMD. [3][4][5][6][7] It has been shown that 30-50% of eyes with RPD will progress to AMD within 5 years 4,8 and RPD have been shown to increase the risk for the development of AMD four-to sixfold when compared to eyes with other stages of age-related maculopathy only. 8,9 In the Beaver Dam Eye Study (BDES), RPD were demonstrated to confer a higher risk of visual impairment.…”
Section: Introductionmentioning
confidence: 99%